MENDORONG PENINGKATAN KINERJA PEGAWAI DENGAN MENGGUNAKAN PERAN KOMUNIKASI, MOTIVASI DAN DISIPLIN KERJA - Joko Wibowo; Bonifasius Nainggolan (Human Capital Development, 2022)
This study aims to determine the role of communication, motivation, and work discipline in improving employee performance. The research hypotheses were tested using multiple linear regression analysis with the help of SPSS 26. The survey was conducted by distributing questionnaires to 133 employees of the Ministry of Tourism and Creative Economy's Deputy for Destination Development and Infrastructure Jakarta. The selection of respondents was carried out using a saturated sample technique because it involved all employees with ASN status. Communication, motivation, and work discipline are all needed to improve employee performance, according to the findings. Communication and work discipline are also important factors in enhancing performance, although motivation is not. The capacity of these three criteria to describe the diversity of employee performance is 57 percent, with the remaining 43 percent described by variables that were not evaluated. This research offers implications for better understanding the impact of communication, motivation, and work discipline on employee performance, particularly ASN, as well as the need to boost employee motivation so that they may contribute to enhancing their own performance.